(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In building construction various regular structures are provided. Irregular structures are also provided during the construction. Due to earthquake various studies should be made for these irregularities. For the minimization of the damage of the structure due to earthquake necessary precautions should be taken during the design phase. Various damages may occur during construction due to seismic excitations. Damage in the structure will not be same due to various configuration, region, etc. The seismic behavior of the structure depends upon structural system, soil location, quality of the construction, earthquake characteristics and its maintenance. In this paper 10 storey building is considered for both regular and irregular structure. Model of the building is done in ETABS-2016. Loads that are considered such as earthquake/ dead/ and live load in both axis for purpose of analysis. Various types of load combinations are taken according to NBC 105:2020. In this paper regular and irregular plan of building are put under various seismic conditions. The primary goal of the paper is to observe the various performances between the models and which will have a better performance between the two. In the present study RCC building models having G+9 stories with regular and irregular plan considered for analysis. The analysis of model is done using dynamic method in ETABS software. At last, the results of seismic behavior of buildings are compared about the base drifts, shear, displacement, member forces, overturning moment, time period, stiffness.